Measures Teachers’ Perceptions of Differentiated Instruction : A Combination of Guttman Scale and Item Response Theory - Desy Kumala Sari; Dadan Rosana; Supahar Supahar; Pri Ariadi Cahya Dinata; Andi Reski (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2024)
This study aims to develop an instrument for teachers’ perceptions of differentiated instruction by adopting Oriondo and Antonio's instrument development model. This study involves three stages of development: instrument planning, pilot testing, and measurement. The respondents involved were 152 subject teachers at the secondary school level. The instrument developed contains differentiated instruction principles: learning environment, quality curriculum, responsive teaching, continuous assessment, and leadership and routines. A combination of the Guttman Scale and Item Response Theory was used to measure teachers' perceptions, which gave significant results. The analysis results show that most instrument items follow the model used, but some items require adjustment. The implication of this study is the importance of developing valid and reliable instruments to measure teachers' perceptions of differentiated instruction. The findings can contribute to improving classroom learning practices and student learning outcomes. Thus, this study provides a strong foundation for the development of teacher professionalism and the overall improvement of education quality.